Family Economic Strengthening and Parenting Stress Among Caregivers of AIDS-Orphaned Children: Results from a Cluster Randomized Clinical Trial in Uganda - Nabunya, Proscovia (2014)
This study examines the impact of a family economic strengthening intervention on parenting stress among caregivers of AIDS-orphaned children in Uganda. The study uses data from a 4-year (2008-2012) NIMH randomized clinical trial for AIDS-orphaned children known as Suubi-Maka (N=346 dyads). Child-caregiver dyads from 10 comparable primary schools were randomly assigned to either the control group (n=167 dyads) receiving usual care for school-going orphaned children (such as food aid and scholastic materials) or the treatment group (n=179 dyads) receiving a family economic strengthening intervention (focused on a matched savings account), financial planning and management workshops over and above the usual care. Interviews were conducted at baseline, 12 months and 24 months follow-up. This study uses data from baseline and 24 months post-intervention. We use multivariate regression methods, controlling for socioeconomic characteristics. At 24 months, caregivers in the treatment group reported significantly lower levels of parenting stress compared to caregivers in the control group. Findings from this study point to the potential of a family economic strengthening intervention to improve caregiver’s psychosocial wellbeing and that of their families. We conclude that programs and policies aimed at improving the psychosocial wellbeing of families caring for AIDS-orphaned children may consider incorporating economic strengthening components in their programming to help support these kinds of families, caregivers of AIDS-orphaned children especially those residing in developing countries.